Reconstruction of Islamic Education in Java: Historical-Pedagogical Study of the Role of Walisongo - Andi Eki Dwi Wahyuni; Bahaking Rama; Syamsuddin Syamsuddin (PT. Anagata Sembagi Education, 2024)
The history of Islamic education in Java not only reflects changes in religious teaching approaches and methods, but also is a mirror of broader changes in Javanese society. Islam first entered Java in the 14th century, precisely in 1399 AD. Islam was introduced by Maulana Malik Ibrahim, an Arab who once lived in Gujarat, India with his nephew named Mahdum Ishaq. He and his nephew were in Gresik, East Java to start spreading Islamic education. Walisongo is reviewed from the personality classified as a lover of Allah when viewed in terms of the strategy of his duties and functions in the Demak kingdom he is the ruler of the government, that's why he obtained the title Walisongo was given the title of